Carcinoembryonic Antigen (CEA) and Cancer Antigen 125 (CA-125) as Diagnostic Biomarkers for Malignant Pleural Effusion - Harsini, Harsini; Kurniawan, Yoseph Dwi; Sutanto, Yusup Subagio (Respiratory Science, 2024)
Background: The etiology of pleural effusion is very important in malignant pleural effusion management and prognosis. Pleural fluid cytology examination is a simple diagnostic tool and has been widely used to differentiate the etiology of pleural fluid with high specificity albeit its relatively low sensitivity. The use of tumor markers for malignant pleural effusion in Indonesia is still sparse. This study was intended to determine the sensitivity and specificity of CEA and CA-125 examinations in diagnosing malignant pleural effusion. Method: This was an observational analytic study with a cross-sectional approach to find the diagnostic value of CA-125 and CEA of pleural fluid in malignant pleural effusion. Subjects were patients with suspicion of malignant pleural effusion who underwent treatment in the emergency room, polyclinic, and inpatient ward at RSDM from October - November 2022. Results: CEA value with a cutoff of ≥32.00 had a sensitivity of 83.3%; specificity of 87.8%; PPV of 90.9%; NPV of 77.8% with an accuracy of 85.0% (P=0.001), a CA-125 value with a cutoff of >152.40 had a sensitivity of 83.3%; specificity 81.3%; PPV 87.0%; NPV 76.5%; with an accuracy of 82.5% (P=0.001). An increase in CEA and CA-125 signified a significant risk of malignant pleural effusion (P<0.05). Patients with increased CEA and CA-125 had 105 times the risk of developing malignant pleural effusion. Conclusion: CEA ≥32.00 and CA-125 >152.40 are potential biomarkers to predict malignant pleural effusion with CEA having better specificity than CA-125.